2013
DOI: 10.1111/asj.12143
|View full text |Cite
|
Sign up to set email alerts
|

Cold exposure increases slow‐type myosin heavy chain 1 (MyHC1) composition of soleus muscle in rats

Abstract: The aim of this study was to examine the effects of cold exposure on rat skeletal muscle fiber type, according to myosin heavy chain (MyHC) isoform and metabolism-related factors. Male Wistar rats (7 weeks old) were housed individually at 4 ± 2°C as a cold-exposed group or at room temperature (22 ± 2°C) as a control group for 4 weeks. We found that cold exposure significantly increased the slow-type MyHC1 content in the soleus muscle (a typical slow-type fiber), while the intermediate-type MyHC2A content was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 70 publications
3
18
0
2
Order By: Relevance
“…Our SDS-PAGE analyses revealed that the soleus muscles (slow twitch fiber dominant muscle) from cold-exposed rats were composed primarily of MyHC1, while those from the control population expressed high levels of MyHC1 but also expressed MyHC2A (Fig 4B left, SDS-PAGE results from published data [24]). Likewise, the staining of cold-exposed and control soleus muscles clearly demonstrated that the cold-exposed tissues were composed entirely of MyHC1 fibers (Fig 4B right).…”
Section: Resultsmentioning
confidence: 53%
See 3 more Smart Citations
“…Our SDS-PAGE analyses revealed that the soleus muscles (slow twitch fiber dominant muscle) from cold-exposed rats were composed primarily of MyHC1, while those from the control population expressed high levels of MyHC1 but also expressed MyHC2A (Fig 4B left, SDS-PAGE results from published data [24]). Likewise, the staining of cold-exposed and control soleus muscles clearly demonstrated that the cold-exposed tissues were composed entirely of MyHC1 fibers (Fig 4B right).…”
Section: Resultsmentioning
confidence: 53%
“…To examine whether our staining method could be applied to the evaluation of muscle fiber type transitions, we analyzed a panel of muscle samples obtained during two of our previous studies [23][24]. In these studies, we assessed alterations in muscle fiber types by SDS-PAGE analysis of muscle tissue homogenates.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…27,28 The activation of PPARd in skeletal muscle of BPE-treated mice could strongly increase the amount of slow-twitch type muscle fiber, which leads to the improvement of exercise endurance by elevating mitochondrial number.…”
Section: Discussionmentioning
confidence: 99%